Hydration properties of nanosilica, modified by adsorbed C60 fullerene. Issue 2 (13th March 2013) - Turov, V.V.; Ugnivenko, A.P.; Krupskaya, T.V.; Prylutskyy, Y.I.; Schütze, C.; Ritter, U.
Abstract The adsorption of water, methane and hydrogen on a nanocomposite surface based on nanosilica A‐300 modified by C60 fullerene by absorption was studied by low‐temperature 1H NMR spectroscopy. The thermodynamic characteristics, the size of the interface water clusters, and co‐adsorption effects of combustible gases, i. e. methane and hydrogen, were determined. The distribution of the adsorbed water clusters radii showed several maxima depending on the environment. In hydrogen atmosphere the maximum amount of water was detected in clusters with radii of less than 2 nm. It was found that in contrast to the original silica, the weakly polar organic compounds and water adsorbed on different parts of the SiO2/C60 nanocomposite surface.